Transporting goods By road - Webb, Michael (London: Weidenfeld and Nicolson [for the] London School of Economics and Political Science, 1972)
Expenditure on road goods transport is already large. So the purpose of this study is to examine what can be done to contain or reverse the established trend of rapid increases in this expenditure.
Includes bibliographical references.
ne 2/03/2018
Loans
Keywords: Transportation, Automotive; Transportation - goods